Heutagogy approach using trello online learning on the critical thinking skills amongst students with different learning styles - Rathakrishnan, Mohan; Raman, Arumugam (IGI Global, 2019)
Trello online discussion has become one of the important strategies for the University Utara Malaysia Management Foundation Programme student to teach other students to think critically in conveying their ideas and become more proactive and creative in critical thinking subject. In a heutagogical approach, learners become highly autonomous and self-determined while learning online. They use Trello online discussion tool as self-determination learning. Trello enable the learners to use their capacity and capability with the goal of producing learners. Trello online learning was conducted to examine its effectiveness in enhancing macro critical thinking among active-reflective learning style. The students discuss and write their ideas in Trello. Ideas that are posted in Trello will be displayed in front of the class so that the entire learners in the class could see the given ideas. Paul's model was used to analyze learners' critical thinking in Trello online discussion.